Rabies in Pakistan: Policies and recommendations - Abdul Jabbar; Attaullah Ahmadi; Nimra Irm; Iqra Naseeb; Shekiba Madadi; Don Eliseo Lucero‐Prisno III (Wiley, 2024)
Abstract Rabies, commonly referred to as the endemic disease of the impoverished in Pakistan, remains a significant public health concern. Globally, it contributes to over 55,000 fatalities annually, with 31,000 cases reported in Asia, predominantly among children. In Karachi, the yearly occurrence of rabies ranges between 7 and 9.8 cases per million individuals. However, the actual burden is likely underestimated due to underreporting. Key challenges in Pakistan include limited awareness and increasing dog bite incidents. To address this, comprehensive educational programs focusing on proper wound care, the ineffectiveness of homemade remedies, the importance of early medical intervention, and the administration of vaccines and post‐exposure prophylaxis are imperative. Implementing a One Health model, encompassing mass vaccination, cost‐effective treatments, training on intradermal vaccine administration, accurate data collection, and community awareness initiatives, is essential for rabies control. This article aims to provide policymakers and scholars with valuable insights into the primary factors and challenges of controlling endemic human rabies in Pakistan and proposes effective strategies for its control, with the ultimate goal of achieving rabies‐free status by 2030.